Effectiveness of Giving Compress Against Reduction of Body Temperature In Children: Systematic Review - Burhan, Nurul Zakiah; Arbianingsih; Rauf, Syamsiah; Huriati (Universitas STRADA Indonesia, 2020)
Background: Fever is a clinical manifestation that is often experienced by sick children. Fever can be dangerous if there is a high fever. Seizures can occur as a result of high fever which is not treated early, causing hypoxia of brain tissue and ultimately damage. According to WHO estimates that around 17 million cases of fever worldwide, there are 600,000 deaths each year.Purpose: This study aimed to find out effective interventions to reduce body temperature in children.Methods: This research used quantitative descriptive design with systematic review approach. The research instrument uses Duffy’s Research Appraisal Checklist Approach.Results: After searching the article, there were 9 articles related to giving warm compresses, 6 articles with the location of administration in the axilla and tepid songe areas (wiping the whole body), 7 articles by giving compresses for 30 minutes and 10 articles with compressed water temperature 37oC.Conclusions: Of the 15 articles that have been traced successfully, the most interventions given were warm compresses in the axilla and tepid sponge areas by giving compresses for 30 minutes and compressed water temperature of 37oC